Effectiveness of the TGT cooperative model in improving collaboration and understanding of biotechnology concepts - Salsabila, Hasna; Yulianti, Evy (Universitas Negeri Yogyakarta, 2026)
The purpose of this study was to determine the effectiveness of the Team Games Tournament (TGT)- type cooperative learning model in improving students’ collaboration and conceptual understanding of biotechnology material in grade X high school. This study used a quasi-experimental design, with a total sample of 69 students, divided into 2 classes: 36 students in the experimental class and 33 in the control class. Collaboration skills data collection used peer assessment questionnaires, while conceptual understanding data collection used multiple-choice tests. The data analysis technique used was inferential statistical analysis, consisting of prerequisite tests (normality and homogeneity) and hypothesis tests (independent-samples t-tests, Mann-Whitney U tests, and Wilcoxon tests). The results of this study indicate that: (1) The use of the Team Games Tournament (TGT) learning model in biotechnology material does not have a significant effect on the collaboration skills of grade X students with an average value in the experimental class of 84.53, while in the control class it was 82.61, with a significance value of 0.521 0.05; (2) The use of the Team Games Tournament (TGT) type cooperative learning model on biotechnology material is effective in improving the conceptual understanding of class X students with an average posttest score in the experimental class of 80, while in the control class it was 72.12, with a significance value of 0.024 0.05. The TGT-type cooperative learning model can be recommended as an alternative learning strategy to improve conceptual understanding of biotechnology at the high school level, particularly by encouraging students’ cognitive engagement through structured competitive activities. However, to optimize the improvement of collaboration skills, modifications to the learning design are needed, such as emphasizing individuals’ roles in groups, strengthening process assessments, and integrating collaborative reflection.